Carbon Based Nanodots in Early Diagnosis of Cancer - Singh, Gurpal; Kaur, Harinder; Sharma, Akanksha; Singh, Joga; Alajangi, Hema Kumari; Kumar, Santosh; Singla, Neha; Kaur, Indu Pal; Barnwal, Ravi Pratap (Frontiers in Chemistry, 2021)
Detection of cancer at an early stage is one of the principal factors associated with successful treatment outcome. However, current diagnostic methods are not capable of making sensitive and robust cancer diagnosis. Nanotechnology based products exhibit unique physical, optical and electrical properties that can be useful in diagnosis. These nanotech-enabled diagnostic representatives have proved to be generally more capable and consistent; as they selectively accumulated in the tumor site due to their miniscule size. This article rotates around the conventional imaging techniques, the use of carbon based nanodots viz Carbon Quantum Dots (CQDs), Graphene Quantum Dots (GQDs), Nanodiamonds, Fullerene and Carbon Nanotubes that have been synthesized in recent years, along with the discovery of a wide range of biomarkers to identify cancer at early stage. Early detection of cancer using nanoconstructs is anticipated to be a distinct reality in the coming years.